2001
DOI: 10.1046/j.1364-727x.2001.00019.x
|View full text |Cite
|
Sign up to set email alerts
|

Milk ingredients as nutraceuticals

Abstract: Cow’s milk is considered as a basic food in many diets, and is rich in a variety of essential nutrients. With today’s sophisticated analytical, biochemical and cell‐biological research tools, the presence of many other (minor) compounds with biological activity has been demonstrated. Achievements in separation techniques in the dairy industry and enzyme technology offer opportunities to isolate, concentrate or modify these compounds, so that their application in functional foods, dietary supplements, nutraceut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 63 publications
1
40
0
7
Order By: Relevance
“…Generally, during the early stage of growth, neonates consume milk from their mothers' breasts for a certain period, but, in other cases, they consume milk from several alternative sources such as milk from domesticated animals, milk powders and artificial milk supplements [PLAYNE, et al 2003]. Although milk from various species, such as cattle, buffalo, sheep, goats and camels, has been studied scientifically for several decades, cow's milk has been proven to have a lot of benefits for human health and nutrition because of its similarity to the composition of human milk [AGOSTONI, et al 2000, LONNERDAL and STKINSON 1995, STEIJNS 2001.…”
Section: Basic Components and Properties Of Milkmentioning
confidence: 99%
“…Generally, during the early stage of growth, neonates consume milk from their mothers' breasts for a certain period, but, in other cases, they consume milk from several alternative sources such as milk from domesticated animals, milk powders and artificial milk supplements [PLAYNE, et al 2003]. Although milk from various species, such as cattle, buffalo, sheep, goats and camels, has been studied scientifically for several decades, cow's milk has been proven to have a lot of benefits for human health and nutrition because of its similarity to the composition of human milk [AGOSTONI, et al 2000, LONNERDAL and STKINSON 1995, STEIJNS 2001.…”
Section: Basic Components and Properties Of Milkmentioning
confidence: 99%
“…The determination of TMs level in milk is particularly monitored by international organizations. (Steijns JM 2001, Licata P et al 2004) Many reports indicated the presence of heavy metals in milk and other food products. (Caggiano R et al 2005, Tuzen M et al 2008) Cu, Zn and Se are essential metals for normal function of our body, however, from the toxicological point of view, their intake in higher amounts above safe recommended levels may be risky to the human health.…”
Section: Introductionmentioning
confidence: 99%
“…80 kDa, containing 1-4 glycans depending on the species. Bovine and human LFs consist of 989 and 691 amino acids, respectively [60]: the former is present to a concentration of ca. 0.1 mg mL -1 [25,61], and is an iron-binding glycoprotein -so it is thought to play a role in iron transport and absorption in the gut of young people.…”
Section: Lactoferrin (Lss)mentioning
confidence: 99%